Heterogenic Distribution of Aromatic L-Amino Acid Decarboxylase Neurons in the Rat Spinal Cord - Ren, Li-Qun; Chen, Meng; Hultborn, Hans; Guo, Sen; Zhang, Yifan; Zhang, Mengliang (Frontiers in Integrative Neuroscience, 2017)
Aromatic L-amino acid decarboxylase (AADC) is an essential enzyme in the synthesis of serotonin, dopamine and certain trace amines and is present in a variety of organs including the brain and spinal cord. It is previously reported that in mammalian spinal cord AADC cells (called D cells) were largely confined to a region around the central canal and that they do not produce monoamines. To date, there has not been a detailed description of their distribution and morphology in mammals. In the present study this issue is systematically investigated using immunohistochemistry. We have found that AADC cells in the rat spinal cord are both more numerous and more widely distributed than previously reported. In the gray matter, AADC neurons immunolabeled for NeuN were not only found in the region around the central canal but also in the dorsal horn, intermediate zone and ventral horn. In the white matter a large number of glial cells were AADC-immunopositive in different spinal segments and the vast majority of these cells expressed oligodendrocyte and radial glial phenotypes. Additionally, a small number of AADC neurons labeled for NeuN were found in the white matter along the ventral median fissure. The shapes and sizes of AADC neurons varied according to their location. For example, throughout cervical and lumbar segments AADC neurons in the intermediate zone and ventral horn tended to be rather large and weakly immunolabeled, whereas those in comparable regions of sacrocaudal segments were smaller and more densely immunolabeled. The diverse morphological characteristics of the AADC cells suggests that they could be further divided into several subtypes. These results indicate that AADC cells are heterogeneously distributed in the rat spinal cord and they may exert different functions in different physiological and pathological situations.